Experimental and Clinical Studies on The Therapeutic Effects of Koryo Medicine-Rapid Coronary Blood Flow Enhancer, Atherosclerosis, and Some Ischemic Heart Diseases - Ri, Chol Yong; Mun, Yong Il; Ri, Mae; Kang, Chol Ho; O, Song Thaek (Medical Science Journal for Advance Research, 2026)
Background and aims: Some Koryo medicines have a very positive effect on cardiovascular diseases such as arteriosclerosis, angina pectoris, myocardial infarction, and acute coronary syndrome by improving coronary blood flow and enhancing cardiac activity. The aim of this study was to investigate the experimental and clinical effects of Koryo medicines, including Carthami flos, Typhae pollen, Ligustici rhizoma, Salviae miltiorrhizae radix, Veratri maximowiczii herba, Epimedii herba, Ginkgo folium, Crataegi fructus, Bupleuri radix, Astragali radix, ivy vine on several cardiovascular diseases. Methods: The composition of "rapid coronary blood flow enhancer": Carthami flos (powder) 0.2, Bupleuri radix (water extract)0.15, Ligustici rhizoma (powder)0.15, Typhae pollen(flour) 0.15, Salviae miltiorrhizae radix(water extract) 0.25, Astragali radix(water extract) 0.25, Veratri maximowiczii herba(water extract) 0.3, Crataegi fructus(powder) 0.3, ivy vine (water extract) 0.3, Epimedii herba(water extract) 0.1, Ginkgo folium(water extract) leaves 0.1 were mixed with honey and prepared by encapsulation to a weight of 0.5g. The experimental animals (Wistar rats) that developed the coronary atherosclerosis model were administered at a dose of 0.6g/kg once daily for 14 days and the experimental parameters were analyzed. Patients with angina pectoris, atherosclerosis, and hypertension were treated with 2 tablet at a time and 3 times a day for 25 days before eating. Results: In coronary atherosclerosis animals and clinical trials, HDL, SOD and CAT activities were significantly elevated, TC, TG, LDL, and LPO levels were significantly decreased (p<0.001), and electrocardiographic findings were significantly improved. Conclusions: The “rapid coronary blood flow enhancer” consisting of several Koryo medicines improves plasma lipids and antioxidant parameters and rapidly relieves clinical symptoms.